2009
DOI: 10.2174/1876823700901010041
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Agonists Down-Regulate the Expression of Atp10c mRNA during Adipogenesis

Abstract: Abstract:We have shown that Atp10c, a type 4 P-type ATPase, is a strong candidate affecting glucose and lipid metabolism in humans and mice. Atp10c is a putative phospholipid translocase associated with cell signaling and intracellular protein trafficking. In order to examine the biological role of Atp10c, semiquantitative reverse transcriptasepolymerase chain reaction was carried out. Atp10c mRNA is expressed in 3T3-L1 cells and in primary preadipocytes and adipocytes generated from mice. Atp10c mRNA is regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Our laboratory has demonstrated that Atp10c heterozygous mice are insulin resistant and have an altered insulin-stimulated response in peripheral tissues. Our obesity mouse model is dietinduced and shows insulin resistance characterized by hyperinsulinemia, hyperglycemia, hyperlipidemia, and obesity in association with glucose intolerance [ 2 , 3 , 11 ]. In fact, a recent publication has sited ATP10C as a potential biomarker for obesity and related metabolic disorders [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our laboratory has demonstrated that Atp10c heterozygous mice are insulin resistant and have an altered insulin-stimulated response in peripheral tissues. Our obesity mouse model is dietinduced and shows insulin resistance characterized by hyperinsulinemia, hyperglycemia, hyperlipidemia, and obesity in association with glucose intolerance [ 2 , 3 , 11 ]. In fact, a recent publication has sited ATP10C as a potential biomarker for obesity and related metabolic disorders [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following procedures were performed as described elsewhere [ 5 , 10 , 11 ]. Cells were washed with ice cold 1X PBS, and total RNAs were isolated using RNeasy Mini RNA kit (Qiagen), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stromal vascular fraction cells from adipose tissue were isolated as previously described with slight modifications [3,18–20]. Adipose tissue was rinsed with a 10% bleaching solution for disinfection and, after washing thoroughly with 1× phosphate‐buffered saline (PBS) a , minced into small pieces.…”
Section: Methodsmentioning
confidence: 99%
“…The medium was changed every 3 days. Adipocytes were stained with Oil Red O after 0, 2, 4 and 6 days, as described previously [20]. For staining, cells were fixed with 10% formalin for 15 min and rinsed with deionised water, followed by the addition of 2 aliquots of 85% propylene glycol h for 5 min each.…”
Section: Methodsmentioning
confidence: 99%